Impact of Green Accounting and the Global Reporting Initiative (GRI) on Firm Value - Reza, Fahry; Juliansyah, Ari; Aliyah, Fatimah; Wulandari, Yulia (Universitas Islam Negeri Raden Intan Lampung, 2024)
The primary objective of this study is to investigate the partial and simultaneous effects of green accounting and the Global Reporting Initiative (GRI) on firm value, specifically focusing on companies listed on the Jakarta Islamic Index (JII) during the period from 2019 to 2022. This research employs a quantitative approach, utilizing statistical methods to analyze the relationships between the variables of interest, thereby providing empirical evidence regarding their impact on firm value. Data for this study is sourced from annual financial reports, sustainability reports, and other relevant documents published by the companies on the JII, along with secondary data from reputable financial databases and publications to support the analysis. The data analysis techniques employed include regression analysis, which assesses the relationships between green accounting, GRI, and firm value, while also examining the moderating effect of media exposure on these relationships. The findings indicate that the green accounting variable does not have a significant effect on firm value, whereas the GRI variable demonstrates a positive impact on firm value. Furthermore, the study reveals that media exposure does not moderate the relationship between green accounting and GRI on firm value. Additionally, the combined effects of green accounting, GRI, and media exposure do not significantly influence firm value. This research acknowledges certain limitations, including the restricted sample size of companies listed on the JII and the specific time frame of the study, which may limit the generalizability of the findings. Future research could expand the sample size and consider additional variables to provide a more comprehensive understanding of the relationship between sustainability practices and firm value, ultimately contributing to the broader discourse on corporate sustainability and its implications for business performance.